2018
DOI: 10.1089/jpm.2018.0169
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Outcomes, and Associated Factors for Opioid-Induced Neurotoxicity in Patients with Advanced Cancer Receiving Opioids in Inpatient Palliative Care

Abstract: Context: Opioid-induced neurotoxicity (OIN) is an underdiagnosed yet distressing symptom in palliative care patients receiving opioids. However, there have been only a limited number of studies on OIN. Objectives: Our aim was to determine the frequency of and risk factors for OIN in patients receiving opioids during inpatient palliative care. Methods: We randomly selected 390 of 3014 eligible patients who had undergone palliative care consultations from January 2014 to December 2014. Delirium, drowsiness, hall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 27 publications
0
14
0
2
Order By: Relevance
“…Symptom management is a key element of palliative care, but many drugs used to control symptoms (e.g., opioids, steroids and anticholinergic drugs) are considered to correlate with delirium (37). Opioids, as the mainstay of cancer pain management, could precipitate delirium by increase dopamine release in the nucleus accumbens through opioid receptors (38,39), which has been confirmed in palliative care population (40)(41)(42). However, the impact of opioid dose on delirium is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Symptom management is a key element of palliative care, but many drugs used to control symptoms (e.g., opioids, steroids and anticholinergic drugs) are considered to correlate with delirium (37). Opioids, as the mainstay of cancer pain management, could precipitate delirium by increase dopamine release in the nucleus accumbens through opioid receptors (38,39), which has been confirmed in palliative care population (40)(41)(42). However, the impact of opioid dose on delirium is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…However, Senel et al reported that the use of opioids (used or not used) was one of the risk factors for delirium among cancer patients in PCUs 17 . Lim et al also found that a high daily morphine equivalent dose at the start of palliative care consultation was positively associated with the incidence of opioid‐induced neurotoxicity, which includes delirium 18 . One possible reason for the different results is that we may have underestimated the prevalence of agitated delirium because our assessment was based on point estimation.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed the presence of agitated delirium on admission and at 3 days before death. To adjust for background factors with a potential influence on the prevalence of agitated delirium at the time of assessment, we collected several other data on the day of enrollment based on previous studies and discussion among researchers, 11,13,[16][17][18][19] including age, gender, Eastern Co-operative Oncology Group Performance Status (ECOG PS), central nervous system metastasis, chemotherapy within a month, use of oxygen therapy, use of any catheter, age-adjusted Charlson Comorbidity Index (ACCI), 20,21 pleural effusion, asities, symptom severity defined by the Integrated Palliative Care Outcome Scale (IPOS), [22][23][24] opioid dosage, usage of antipsychotics, usage of benzodiazepines, data to formulate Prognosis in Palliative Care Study predictor models-A (PiPS-A), 25,26 site of primary cancer, metastatic site, Abbreviated Mental Test judged by the physician, heart rate, anorexia, dysphagia, dyspnea, and weight loss in the previous month. We assessed the symptom severity of pain, shortness of breath, weakness or lack of energy, drowsiness, and sore or dry mouth using IPOS, which was scored as 0 (not at all), 1 (slight), 2 (moderate), 3 (severe), and 4 (overwhelming), and defined the prevalence as any IPOS symptoms specified as 2 (moderate), 3 (severe), or 4 (overwhelming).…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Opioid-induced AEs include constipation, nausea, respiratory depression, delirium and somnolence. 4) Furthermore, "opioid-induced neurotoxicity (OIN)" is a distressing symptom in palliative care patients receiving opioids. 5) Symptoms of OIN include delirium, drowsiness, hallucinations, myoclonus and seizures.…”
Section: Introductionmentioning
confidence: 99%